Image Generation for Moina Classification using GAN-CNN and Digital Holography - Bunyarit Voochaiyaphum; Prathan Buranasiri; Witoon Yindeesuk (My University, 2024)
Moina are small aquatic organisms that cannot be differentiated by species with the naked eye. In this research, we employed the GAN-CNN technique to generate images of Moina from raw hologram data and to automatically classify the species. The experimental results demonstrate the effectiveness of the GAN-CNN technique for species classification.
Keywords: Digital Holography and Microscopy; Image Processing Techniques and Applications; Advanced Optical Imaging Technologies